Implementation of Interactive Modules using Problem-Based Learning Models in Programming Algorithm Courses - Ramadhan, Juniawan; Sutopo, Yeri; Wahyuningsih, Sri Endah (Universitas Negeri Semarang, 2025)
This research is based on the problem of low logical thinking skills of PTIK students in programming algorithms, and cannot be optimized through traditional teaching methods. the main thing of the research is to design and assess interactive modules based on the Problem Based Learning (PBL) model to improve the logical thinking skills of PTIK students. The research method used is the Research and Development (R&D) approach with the ADDIE model which includes the stages of Analysis, Design, Development, Implementation and Evaluation. These stages involve determining needs, organized planning, digital product development, implementation in a real learning context, and thorough evaluation. The resulting module combines the features of a live coding editor to support practice. The findings of this study indicate that this interactive module is very useful and practical to implement. Expert validation confirmed that in terms of functionality, ease of use, reliability and efficiency, the module has good quality, and the module also proved successful in improving the logical thinking skills of PTIK students. In conclusion, the PBL-based interactive module can be considered as a practical and effective learning tool. The new discovery in this research is the provision of an innovative integrated digital learning solution, which directly supports the improvement of logical thinking skills in the field of programming.